Proportions of Examinees Undergoing Mass Screening Examination for Breast Cancer and its Preventive Effects Against Breast Cancer Death - Ito, Sueyoshi; Yoshida, Mitsugu; Izumi, Kisaku (Journal of Japan Association of Breast Cancer Screening, 1995)
The contribution of the current mass screening examination involving inspection and palpation to the reduction of breast cancer death was studied. We investigated the relationship between standard mortality rates (SMRs) by cities, towns and villages and the proportions of the examinees undergoing mass examination among all relevant subjects. In Kochi prefecture, mass screening examination for breast cancer was initiated in 1973, and the proportion of examinees who underwent the examination in 1993 accounted for 16.6% of all relevant subjects over 30 years of age (under the Health Service Law for the Aged, 21.6%). The proportions of examinees varied according to cities, towns and villages as follows : less than 15% in 12 cities, towns and villages, 15-25% in 25, and higher than 25% in 16. The SMR for breast cancer in Kochi prefecture decreased from 90-95 (national average : 100) at the start of mass examination to slightly less than 80. The number of cities, towns and villages with an SMR of less than 80 was six (50.0%) out of the 12 in which the proportion of the examinees was less than 15%. The number was increased, however, to 31 (75.6%) of the 41 cities, towns and villages in which the proportion of the examinees was 15% or higher. These results suggest that mass screening examination for breast cancer by inspection and palpation performed in 15% or more of all relevant subjects, provides sufficient preventive effects against breast cancer death.